Design and magneto‐optical characteristics of Ge–Sb–S–PbI2 chalcogenide glasses with a high Verdet constant. Issue 11 (27th May 2019) - Xu, Yantao; Guo, Haitao; Liu, Xiaogang; Cui, Jian; Xiao, Xusheng; Cui, Xiaoxia; Guo, Junjiang; She, Jiangbo; Lu, Min; Peng, Bo
Abstract: To develop high‐performance magneto‐optical chalcogenide glasses and clarify the mechanisms of the Verdet constant, a series of GeS2 –Sb2 S3 –PbI2 chalcogenide glasses were designed and fabricated, and their Faraday effects were investigated at a wavelength of 980 nm. A new parameter, that is, average polarizability, was proposed, and the results show that the Verdet constant has a good linear relationship with average polarizability, meaning that the Verdet constant of a chalcogenide glass can be directly estimated by its chemical constituents. The Verdet constant is as large as 0.200 min G −1 cm −1 at 980 nm for 22.5GeS2 –67.5Sb2 S3 –10PbI2 composition glass, which is the largest value reported thus far for sulfide glasses; this glass also possesses good thermal and optical properties and therefore might be an attractive candidate for mid‐infrared magneto‐optical device applications.